Living With and Beyond Cancer With Comorbid Conditions: Qualitative Insights to Understand Psychosocial Support Needs. - Cavers, Debbie; Cunningham‐Burley, Sarah; Watson, Eila; Banks, Elspeth; Campbell, Christine (Health Expectations, 2024)
Introduction: There is a pressing need to understand and explore the complex experiences and psychosocial support needs of people LWBC‐CM and their informal caregivers, to inform survivorship and supportive care interventions. Methods: In‐depth qualitative interviews were conducted with people LWBC‐CM and their informal caregivers in Scotland, invited via primary care. One‐to‐one, face‐to‐face interviews were conducted with informed consent exploring experiences of symptoms, psychosocial support needs and interactions with health services. Interviews were transcribed and analysed using a thematic approach. Results: Forty‐one people LWBC‐CM and twenty‐three informal caregivers were interviewed. Four themes were identified: the Physical and Psychological Impact of Cancer and Comorbidity, Dominant Storie—Prioritising Conditions and Making Sense of Illness, Navigating Health Services and Treatments and Caring for People with Complex Health Conditions. Type and severity of conditions mediated people's experiences and daily living. Complex fatigue—fatigue arising from a number of health conditions—dominated symptomology. Participants navigated multiple appointments and complex medication regimes. Patients identified the need for acknowledgement of other chronic conditions and for streamlined care provision. Mutual caring and social isolation were also identified as part of the caring relationship. Conclusions: There is a mandate to address the psychosocial support needs of people LWBC‐CM, and their informal carers, given the burden of treatment for cancer survivors with moderate to severe complex conditions as they navigate health services. Patient or Public Contribution: A patient representative has been involved in all stages of the study from development of the application through study design, commenting on documentation, analysis of transcripts and writing the manuscript. They are included as an author on the manuscript. Practitioner Point: Existing work to expand cancer survivorship models of care to incorporate other chronic conditions, and integrated models of care for multimorbidity, can work together to create coherent, patient‐centred quality provision of care for cancer survivors.